Punicalagin Regulates Key Processes Associated with Atherosclerosis in THP-1 Cellular Model - Sanaa Almowallad; Etimad Huwait; Rehab Al-Massabi; Salma Saddeek; Kalamegam Gauthaman; Alexandre Prola (MDPI AG, 2020)
Atherosclerosis may lead to cardiovascular diseases (CVD), which are the primary cause of death globally. In addition to conventional therapeutics for CVD, use of nutraceuticals that prevents cholesterol deposition, reduce existing plaques and hence anti-atherosclerotic effects of nutraceuticals appeared to be promising. As such, in the present study we evaluated the beneficial effects of punicalagin, a phytochemical against an atherosclerotic cell model in vitro. Cytotoxicity assays were examined for 10 µM concentration of punicalagin on THP-1 macrophages. Real-time-polymerase chain reaction (RT-PCR) was used to analyze monocyte chemoattractant protein-1 (MCP-1) and Intercellular adhesion molecule (ICAM-1) expressions. Monocyte migration and cholesterol efflux assays were performed to investigate punicalagin's further impact on the key steps of atherosclerosis. Cytotoxicity assays demonstrated no significant toxicity for punicalagin (10 µM) on THP-1 macrophages. Punicalagin inhibited the IFN-γ-induced overexpression of MCP-1 and ICAM-1 in macrophages by 10 fold and 3.49 fold, respectively, compared to the control. Punicalagin also reduced the MCP-1- mediated migration of monocytes by 28% compared to the control. Percentages of cellular cholesterol efflux were enhanced in presence or absence of IFN-γ by 88% and 84% compared to control with 58% and 62%, respectively. Punicalagin possesses anti-inflammatory and anti-atherosclerotic effects. Punicalagin also did not exhibit any cytotoxicity and therefore can be considered a safe and potential candidate for the treatment and prevention of atherosclerosis.